The Impact of Booklet-Based Nutrition Counseling on Knowledge and Nutritional Attitudes among Inpatients with Type 2 Diabetes Mellitus at a District Hospital in Southwest Aceh - Aishwarya, Thyara; Fitri, Yulia (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by insufficient insulin production or the body’s inability to effectively utilize insulin. In Indonesia, the prevalence of diabetes mellitus in 2023 reached 1.7%, while in Aceh Province it was 1.6% of the total population. In Southwest Aceh District, there were 5,339 reported cases of diabetes mellitus. This study aimed to develop a booklet as a nutrition counseling medium and to evaluate its effect on nutritional knowledge and attitudes among hospitalized patients with type 2 diabetes mellitus at the Southwest Aceh District General Hospital. The study was conducted in two phases. The first phase involved booklet development using a Research and Development (R&D) approach. The second phase employed a quasi-experimental design with a one-group pre-test–post-test approach. A total of 22 respondents were selected using the Lemeshow formula. The study was conducted at Teungku Peukan District General Hospital, Southwest Aceh District, in December 2024. Data were analyzed using normality tests and dependent t-tests with a 95% confidence level (p < 0.05). The results showed that the mean knowledge score increased from 36.81 before nutrition counseling to 71.13 after counseling (p = 0.000). Similarly, the mean attitude score increased from 34.54 before the intervention to 48.09 after the intervention (p = 0.000). These findings indicate that booklet-based nutrition counseling significantly improves nutritional knowledge and attitudes among patients with type 2 diabetes mellitus.